PENGARUH ETIKA, KOMITMEN ORGANISASI DAN PENEKANAN ANGGARAN TERHADAP BUDGETARY SLACK (Studi Pada OPD Kota Pekanbaru) - Tifanny, Putri Dwi; Edfan, Darlis; Kennedy, Kennedy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to examine (1) the effect of ethic on budgetary slack. (2) the effect of organizational commitment on budgetary slack. (3) the influence of budget emphasis on budgetary slack on the organization of the city apparatus in Pekanbaru. The research method used is a quantitative research method with primary data obtained from questionnaire data measured using a Likert scale. The population in this study were employees of all OPD cities in Pekanbaru. A sample of 120 respondents. The respondent is a budget management apparatus, namely the head of the regional apparatus organization as the user of the budget, the head of the finance, and the sub of programming at each regional apparatus organization as many as 43 regional apparatus organizations in the city of Pekanbaru. Data collection was carried out through a survey using a questionnaire that was distributed to respondents. This research uses multiple linear analysis method with SPSS version 22. The results of this study showed that : 1)Ethic had affect on budgetary slack, 2)Organizational Commitment had no affect on budgetary slack, and 3)Budget Emphasis had effect on budgetary slack in Pekanbaru City Organizations (OPD).Keywords: Ethic, Organizational Commitment, Budget Emphasis, Budgetary Slack